L’ ANTHROPOLOGIE HISTORIQUE DE L’ANTIQUITÉ DANS L’UNIVERSITÉ DE BUCAREST – DE LA DISCIPLINE SUBVERSIVE DES ANNEES 1980 À L’ÉCOLE HISTORIOGRAPHIQUE DE L’APRÈS-COMMUNISME (Analele Universității din București - Istorie, 2024)
The influence of cultural anthropology in Romania, more precisely in the historiographical school from Bucharest, is directly associated with the activity of a small group of very influential professors at the Faculty of History, in the University of Bucharest. This article evokes the atmosphere in the Faculty during the last decade of the communist regime, discussing the ideological ambiguities and contradictions that allowed a semi-subversive, but systematic use of methods and concepts specific to French and American cultural anthropology, especially for the study of Antiquity and the Middle Age.
Keywords: cultural anthropology; ancient history; Romanian historiography